Near‐Infrared Nonfullerene Acceptors Based on Benzobis(thiazole) Unit for Efficient Organic Solar Cells with Low Energy Loss. Issue 12 (16th August 2019) - Li, Shuixing; Zhan, Lingling; Lau, Tsz‐Ki; Yu, Zhi‐Peng; Yang, Weitao; Andersen, Thomas R.; Fu, Zhisheng; Li, Chang‐Zhi; Lu, Xinhui; Shi, Minmin; Chen, Hongzheng
Abstract: The simultaneous achievement of a low energy loss and high external quantum efficiency (EQE) response is the prerequisite for high power conversion efficiencies of organic solar cells (OSCs). Herein, this issue is examined through the design of two novel near‐infrared (NIR) nonfullerene acceptors (X‐PCIC and X1‐PCIC) with an absorption extending to 900 nm, which is realized by using benzobis(thiazole) unit as the core. This study reveals that benzobis(thiazole) unit with the quinoid‐resonance effect and electron‐withdrawing property is a good building block in extending absorption and maintaining suitable energy levels. Single crystal cultivation proves the function of S···N noncovalent interaction in locking molecular geometry. Besides, through adopting two different terminals (fluorinated terminal for X‐PCIC and thiophene‐fused terminal for X1‐PCIC), it is found that an increase in the J‐aggregation strength has a significant positive effect on the EQE response of the devices through the formation of more suitable domain sizes and crystallinity in the films, while the energy loss remains low (≈0.53 eV) and unaffected. Thus, a high efficiency of 11.50% is presented for OSC based on the X‐PCIC with stronger J‐aggregation strength, better than that (10.17%) based on the X1‐PCIC with weaker J‐aggregation strength. This work clearly demonstrates the application of benzobis(thiazole) unit in efficient small molecule acceptors and the importance of J‐aggregation modulation for the simultaneous achievement of low energy loss and high EQE response. Abstract : Near‐infrared nonfullerene acceptors (X‐PCIC and X1‐PCIC) are designed and synthesized by using benzobis(thiazole) unit as the core. It is found that X‐PCIC with stronger J‐aggregation is the better choice to simultaneously achieve low energy loss and high quantum efficiencies. Thus, a high efficiency of 11.50% and a high current density over 21 mA cm −2 are realized for X‐PCIC‐based organic solar cells.